Penerapan Strategi dan Rencana Pemasaran di Sektor Publik: Tinjauan Kontemporer terhadap Efektivitas Implementasi dan Relevansi Kontekstual - Lusia Lestina Halawa; Mira Sukma; Evlin Limbong; Wahjoe Pangestoeti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The transformation of public governance has encouraged a paradigm shift in public service delivery, from an administrative and procedure-oriented approach toward a citizen-centered and value-based model. In this context, public sector marketing has emerged as a strategic instrument to enhance service quality, institutional image, public participation, and trust. This study aims to examine the contemporary implementation of marketing strategies and planning in the public sector, with particular attention to their effectiveness and contextual relevance. The research adopts a qualitative descriptive approach through a systematic literature review of selected scholarly publications addressing public sector marketing, strategy implementation, digital governance, and public service management. The findings indicate that public institutions increasingly apply marketing principles not as commercial activities, but as mechanisms for creating public value through strategic communication, digital engagement, institutional branding, and stakeholder collaboration. However, the effectiveness of implementation varies across organizations and is strongly influenced by leadership capacity, human resources competence, organizational culture, and technological support. The study also reveals that public sector marketing strategies must be adapted to social, cultural, and institutional contexts, as private-sector models cannot be directly transferred. Theoretically, this study strengthens the positioning of marketing as an integral component of public governance. Practically, it provides insights for public organizations to develop contextual, responsive, and sustainable marketing strategies to improve public service performance and trust.